The Relationship between Adiposity and Insulin Sensitivity in African Women Living with the Polycystic Ovarian Syndrome: A Clamp Study. (8th September 2016) - Doh, Emmanuella; Mbanya, Armand; Kemfang-Ngowa, Jean Dupont; Dohbit, Sama; Tchana-Sinou, Mycilline; Foumane, Pascal; Donfack, Olivier Trésor; Doh, Anderson S.; Mbanya, Jean Claude; Sobngwi, Eugene
Abstract : Objectives . We aimed to assess the variation of insulin sensitivity in relation to obesity in women living with PCOS in a sub-Sahara African setting. Methods . We studied body composition, insulin sensitivity, and resting energy expenditure in 14 PCOS patients (6 obese and 8 nonobese) compared to 10 matched nonobese non-PCOS subjects. Insulin sensitivity was assessed using the gold standard 80 mU/m 2 /min euglycemic-hyperinsulinemic clamp and resting energy expenditure was measured by indirect calorimetry. Results . Insulin sensitivity adjusted to lean mass was lowest in obese PCOS subjects and highest in healthy subjects (11.2 [ 10.1–12.4] versus 12.9 [ 12.1–13.8] versus 16.6 [ 13.8–17.9], p = 0.012 ); there was a tendency for resting energy expenditure adjusted for total body mass to decrease across the groups highest in obese PCOS subjects (1411 [ 1368–1613] versus 1274 [ 1174–1355] versus 1239 [ 1195–1454], p = 0.306 ). Conclusion . In this sub-Saharan population, insulin resistance is associated with PCOS per se but is further aggravated by obesity. Obesity did not seem to be explained by low resting energy expenditure suggesting that dietary intake may be a determinant of the obesity in this context.